The Decentralised Central Bank: Regional Bank Rate Autonomy in Norway, 1850-1892 - Jan Tore Klovland; Lars Fredrik Øksendal (Norges Bank, 2015)
Before 1893 the regional branches of Norges Bank set their own bank rates. We discuss how bank rate autonomy could be reconciled with the fixed exchange rate commitments of the silver and gold standard. Although the headquarters of the bank was in Trondhjem, we find that the Christiania branch played the key role in providing leadership in bank rate policy. Foreign interest rate impulses were important for bank rate decisions, but there was also some leeway for responding to idiosyncratic shocks facing the Norwegian economy.
hdl:11250/2495804
Keywords: E58; N23; 330; bank rate; gold standard; monetary policy